2020
DOI: 10.1021/acsapm.0c00444
|View full text |Cite
|
Sign up to set email alerts
|

Scratch-Resistant Porous Polymer Coatings with Enhanced Adhesion to Planar and Curved Substrates

Abstract: Porous polymer coatings are useful for a broad range of applications including textiles, membranes, and implants. For practical applications, it is critical to have good adhesion between the substrate and the porous polymer coating. We report a solvent-free fabrication technique to create porous polymer coatings with excellent adhesion to a wide range of substrates including rigid, flexible, planar, and curved surfaces. These robust porous coatings can withstand tape tests and scratch tests. The porous coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…It is noteworthy that after the PVE brushes grown from the substrate, the peaks of C, Si, and O shifted to some extent, as shown in Figure A–C. The deconvolution of the C 1s signal clearly shows four different components with binding energies of about 284.23, 284.68, 285.21 and 285.78 eV, attributed to ((CH 3 )–O−) n , −C­(O)­C­(CH 2 )­CH 3 –, −CH­(C­(O)­OCH 3 )–, and −(CH 2 CH 2 ) n , respectively, in Figure D. , Additionally, the Si signal can be deconvoluted into four peaks at about 101.13, 102.1, 102.49, and 103.1 eV, assigned to (Si­(OCH 2 )­CH 3 −) n , -Si­(CH 3 ) 2 O-, (−CH 2 -Si­(OCH 3 ) 3 −) n , and SiO 1.78 in Figure E. , Moreover, the characteristic O signals at 531.72, 532.15, and 532.64 eV correspond to −C­(O)­CHC­(O), (−CH 2 CH­(C­(O)­CH 3 )−) n , and −OCH 2 CH 3 -OH in Figure F . In brief, these results confirm the successful chemical tethering of PVE brushes on the substrates.…”
Section: Resultsmentioning
confidence: 91%
“…It is noteworthy that after the PVE brushes grown from the substrate, the peaks of C, Si, and O shifted to some extent, as shown in Figure A–C. The deconvolution of the C 1s signal clearly shows four different components with binding energies of about 284.23, 284.68, 285.21 and 285.78 eV, attributed to ((CH 3 )–O−) n , −C­(O)­C­(CH 2 )­CH 3 –, −CH­(C­(O)­OCH 3 )–, and −(CH 2 CH 2 ) n , respectively, in Figure D. , Additionally, the Si signal can be deconvoluted into four peaks at about 101.13, 102.1, 102.49, and 103.1 eV, assigned to (Si­(OCH 2 )­CH 3 −) n , -Si­(CH 3 ) 2 O-, (−CH 2 -Si­(OCH 3 ) 3 −) n , and SiO 1.78 in Figure E. , Moreover, the characteristic O signals at 531.72, 532.15, and 532.64 eV correspond to −C­(O)­CHC­(O), (−CH 2 CH­(C­(O)­CH 3 )−) n , and −OCH 2 CH 3 -OH in Figure F . In brief, these results confirm the successful chemical tethering of PVE brushes on the substrates.…”
Section: Resultsmentioning
confidence: 91%
“…Freestanding porous polymer films have applications as filters, membranes, tissue scaffolds, and drug delivery systems. , The spongelike structure is advantageous for biological applications because high porosity and pore interconnectivity allow for high drug loading capacity. , To fabricate freestanding polymer sponges that have pH-dependent swelling, the crosslinker molecule ethylene glycol diacrylate (EGDA) was introduced simultaneously with MAA during the fabrication process to form chemical crosslinks to prevent dissolution. It has been shown that increasing the degree of crosslinking with EGDA improves mechanical properties. , We have previously shown that crosslinking with EGDA increases the mechanical strength of the porous pillared PMAA coating to prevent cracking of the coating after thermal annealing when deposited on flexible substrates such as polynorbornene rubber . For this study and for practical bioapplications, a limited degree of crosslinking is preferred to prevent dissolution while maintaining the properties of the primary polymer .…”
Section: Resultsmentioning
confidence: 97%
“…For applications such as oil/water separation and wound dressings, , it is important for the porous coating to have good adhesion to the underlying substrate. We have previously shown that we can increase the adhesion of the pillared coatings shown in Figure a to underlying substrates through the incorporation of the epoxide-containing glycidyl methacrylate (GMA) monomer into the fabrication process . We examined whether this approach could also work to enhance the adhesion of sponge coatings to the underlying substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with studies that have shown that the adhesion of acrylic polymers is improved by cross-linking. 39,40 In addition to increasing the robustness of the polymer coatings, the incorporation of EGDA into the coatings allows for hydrogen bonding between the ethylene glycol polar functionalities and the hydroxyl groups of the metal oxide layer of the stainless steel.…”
Section: ■ Discussionmentioning
confidence: 99%